HUBUNGAN ANTARA KEMAMPUAN MATEMATIKA TERHADAP HASIL BELAJAR FISIKA SISWA SMA - Ramadan, Muhammad; Putri Wulandari, Refika Aulia; Hasanah, Nur; Zahra, An'Nisa Nur; Ikmawati, Ikmawati; Kurniawan, Kurniawan (Universitas Tanjungpura, 2025)
Mathematics and physics are two interrelated disciplines, particularly at the high school level, where mathematical ability serves as a critical foundation for understanding physics concepts. This study aims to examine the relationship between students